Dois ensaios sobre os efeitos da atividade mineradora nos municípios baianos - Oliveira, Antonio Zacarias Batista de (2019)
The present dissertation is composed of two independently structured essays that provide analyzes on the nature of the effects of the application of mining royalties in the process of development of the Bahia municipalities. Although they are related, the first one analyzes the nature of such effects in the evolution of the levels of municipal socioeconomic development between 2005 and 2015. In addition to discussing the impacts of extractive industry on socioeconomic development, adopts as a methodological strategy an econometric linear model of panel data for fixed effects in order to verify if there is correlation between collection, use of CFEM and increases in levels of municipal development. The model has the Firjan Municipal Consolidated Development Index (IFDM GERAL) as explained variable, and as explanatory variables, the values collected from CFEM and Municipal GDP, both divided by the municipal population. It also includes a categorical variable to differentiate the collecting municipalities from non-collectors of CFEM. The results indicate that, although multiple regressions were significant at all levels of significance, the weights of the explanatory variables are very small. Including the categorical variable, this suggests that there is not much difference between collecting and non-collecting municipalities. In turn your, the second essay analyzes the nature of the effects of the application of mining royalties on the efficiency of the municipalities of Bahia, with respect to the promotion of economic development between 2010-2015. For this purpose, is adopted as a methodological strategy the Data Envelopment Analysis (DEA) or Frontier Analysis, with variable effects at the product-oriented scale (BCC) and combined with the methodology of the Malmquist Index of productivity, enabling a intertemporal analysis. The model had the input variable the Municipal Revenue CFEM / APU ratio and the IFDM - Education, IFDM - Employment and Income and the IFDM – Health. The results obtained suggest that the collecting counties studied in the majority (approximately 75%) were efficient, although they did not obtain significant increases in their levels of development.